2001
DOI: 10.1002/1615-9861(200107)1:7<871::aid-prot871>3.3.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

The use of glass wool as an attachment surface for studying phenotypic changes in Pseudomonas aeruginosa biofilms by two-dimensional gel electrophoresis

Abstract: Two-dimensional polyacrylamide gel electrophoresis was used to demonstrate phenotypic differences between Pseudomonas aeruginosa biofilm cells and the planktonic counterpart cells under defined culture conditions. Glass wool was used as a substratum for cell attachment as it affords a large surface-to-volume ratio (1 g with a mean diameter of 15 microns = 1300 cm2), supports the growth of biofilms, allows for free movement of cells between the inter-strand spaces, and it facilitates the exchange of nutrients a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 0 publications
1
26
0
Order By: Relevance
“…Thus, DNA arrays provide a sensitive but transient snapshot of gene expression and proteomics provide a partial sight of protein expression directly correlated with phenotype. While changes in protein expression during biofilm development have been investigated for a large panel of bacterial species (Arevalo-Ferro et al 2005;Dykes et al 2003;Oosthuizen et al 2001Oosthuizen et al , 2002Sauer et al 2001Sauer et al , 2002Steyn et al 2001;Svensä ter et al 2001;Tré moulet et al 2002a;Vilain et al 2004 a, b, c), a limited number of studies have been conducted to determine the impact of the sessile mode of life on E. coli protein expression (Perrot et al 2000;Perrot et al 2001;Tré moulet et al 2002b). These studies have revealed some alterations in the bacterial protein profiles ranging from 3% to more than 50% of the detected protein spots, which gives evidence of significant physiological differences between planktonic and sessile bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, DNA arrays provide a sensitive but transient snapshot of gene expression and proteomics provide a partial sight of protein expression directly correlated with phenotype. While changes in protein expression during biofilm development have been investigated for a large panel of bacterial species (Arevalo-Ferro et al 2005;Dykes et al 2003;Oosthuizen et al 2001Oosthuizen et al , 2002Sauer et al 2001Sauer et al , 2002Steyn et al 2001;Svensä ter et al 2001;Tré moulet et al 2002a;Vilain et al 2004 a, b, c), a limited number of studies have been conducted to determine the impact of the sessile mode of life on E. coli protein expression (Perrot et al 2000;Perrot et al 2001;Tré moulet et al 2002b). These studies have revealed some alterations in the bacterial protein profiles ranging from 3% to more than 50% of the detected protein spots, which gives evidence of significant physiological differences between planktonic and sessile bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…Protein [14][15][16] and LPS [2] profiles also undergo changes in a bacterial cell when it switches from planktonic to sessile form of growth.…”
Section: Introductionmentioning
confidence: 99%
“…The cells from a glass flask, a substratum that does not support biofilm formation by IHE 3034-Rif, were used as a reference, as an inoculum, and were defined as 'inoculate' cells; the cells in the glass flasks at the end of the incubation periods were termed 'planktonic' cells. The non-attached cells removed from the PVC wells after biofilm growth were defined as 'surface-influenced planktonic (SIP)' cells, according to Steyn et al (2001), and the surface-attached cells harvested from the walls of the PVC wells were termed 'biofilm' cells (see Methods). After 24 or 48 h of static growth in M63 medium at 20 u C, the mean Mat expression levels of the entire cell populations were quantified by whole-cell ELISA.…”
mentioning
confidence: 99%